Mobi parking navigator system - Mohamad Nazwan, Shafie (2013)
Parking space it is very important to park the vehicle, the existing car parking system in FSKKP required the driver to find out free parking space to park their car. The increasing the number of car can cause the number parking space become decrease. As the result the driver need to waste their time to circle the parking lot area to find out the free parking space to park their car. This paper investigates about problem and the weakness about the parking that exits in the FSKKP and finally it proposed the Mobi Parking Navigator System (clientside) to prevent this problem from occurs again. The implementation of this mobi apps system can show about the information of the parking space that is available or not available. These mobi apps will support android as a platforms of the mobi operating system to easy to use it The result of the of this mobi apps will reduce time to find the parking lot and easy to know where is the parking lot still available to park the car.